One Example of a Policy Entrepreneur in Postsecondary Education - Whelley, Teresa (Disability Studies Quarterly, 2002)
Students with disabilities have begun to attend postsecondary education in increasing numbers during the past decade, partially due to the changes brought about by the American with Disabilities Act of 1990. This article is one student's story from the beginning of the 1990s and what she did to find and create accommodations at a college. Participant observation and focused interviews were used to obtain the information. Several theoretical explanations are given of her actions and conclusions drawn.